Lexical Ambiguity in Social Crime Issues News in the《国际日报》Guójì Rìbào Newspaper, April 2025 Edition - Aiko Dzata Lini; Subandi Subandi; Lyu Chen (Universitas Negeri Surabaya, 2026)
Lexical ambiguity where a single word licenses multiple meanings can obscure interpretation in Mandarin news, especially in brief, information-dense crime reporting; however, empirical descriptions of how ambiguity is realized and triggered in social-crime news discourse remain limited. Addressing this gap, this study investigates lexical ambiguity in social crime issues news published in the April 2025 edition of the Mandarin-language newspaper 《国际日报》 (Guójì Rìbào), with three objectives: (1) to classify the types of lexical ambiguity, (2) to identify factors that cause ambiguity, and (3) to explicate the lexical meanings generated in context. Using a qualitative descriptive design, the data were collected through document analysis of crime news texts and were examined by (i) isolating ambiguous lexical items, (ii) assigning ambiguity types based on Ullmann’s framework, (iii) tracing ambiguity triggers using Hurford and Heasley’s factors, and (iv) interpreting meanings through contextual, co-textual, and idiomatic cues. The analysis yielded 68 instances of lexical ambiguity, dominated by polysemy (58 cases), followed by homograph (9) and homophone (1), with no homonym cases identified. Two causal patterns were observed: unclear reference (5 cases) and ambiguous phrase/sentence structure (63 cases), indicating that ambiguity is more often driven by condensed journalistic constructions than by referential uncertainty alone. Overall, the ambiguities produced literal, contextual, and idiomatic meaning alternatives, implying that accurate comprehension of Mandarin crime news relies heavily on contextual anchoring and syntactic parsing; these findings support the need for clearer referential specification in news writing and for targeted instruction on disambiguation strategies in Mandarin reading.